Prototype of automatic security and control system for smart home using ESP32 microcontroller - Moh. Iqbal; Alhagie Hydara (Journal of Emerging Innovations in Engineering, 2025)
Despite advances in Internet of Things (IoT) technology, IoT-based home security systems still face challenges in responsiveness and real-time threat detection. Most existing smart home systems focus on energy efficiency while rarely integrating essential security features into a unified platform. This study designed and implemented an automatic smart home security system prototype integrating three subsystems—smart door lock, window security, and LPG gas leak detection—based on the ESP32 microcontroller connected to the Blynk application. Using a quantitative experimental approach, the system was tested through simulated household security scenarios, with data analyzed using Microsoft Excel and MATLAB. Results demonstrated a 99% operational success rate, 1.5-second average response time for gas detection and notification delivery, 98% gas sensor accuracy, and 99.2% data transmission success rate. The system successfully integrated the MQ-135 sensor, keypad-based smart lock, and window sensors into a centralized platform accessible remotely via Wi-Fi. This research contributes to embedded system and IoT technology advancement by providing a low-cost, scalable solution for smart home security with potential applications in small- and medium-scale industrial environments and future enhancement through AI and machine learning integration.